Sterilizing Immunity against SARS‐CoV‐2 Infection in Mice by a Single‐Shot and Lipid Amphiphile Imidazoquinoline TLR7/8 Agonist‐Adjuvanted Recombinant Spike Protein Vaccine. Issue 17 (11th March 2021) - Jangra, Sonia; De Vrieze, Jana; Choi, Angela; Rathnasinghe, Raveen; Laghlali, Gabriel; Uvyn, Annemiek; Van Herck, Simon; Nuhn, Lutz; Deswarte, Kim; Zhong, Zifu; Sanders, Niek N.; Lienenklaus, Stefan; et al.
Abstract: The search for vaccines that protect from severe morbidity and mortality because of infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the virus that causes coronavirus disease 2019 (COVID‐19) is a race against the clock and the virus. Here we describe an amphiphilic imidazoquinoline (IMDQ‐PEG‐CHOL) TLR7/8 adjuvant, consisting of an imidazoquinoline conjugated to the chain end of a cholesterol‐poly(ethylene glycol) macromolecular amphiphile. It is water‐soluble and exhibits massive translocation to lymph nodes upon local administration through binding to albumin, affording localized innate immune activation and reduction in systemic inflammation. The adjuvanticity of IMDQ‐PEG‐CHOL was validated in a licensed vaccine setting (quadrivalent influenza vaccine) and an experimental trimeric recombinant SARS‐CoV‐2 spike protein vaccine, showing robust IgG2a and IgG1 antibody titers in mice that could neutralize viral infection in vitro and in vivo in a mouse model. Abstract : Amphiphilic TRL7/8 agonist adjuvanted recombinant Spike protein vaccine protects against SARS‐CoV‐2 infection in mouse models.